SPATIAL-ELECTORAL ANALYSIS OF THE PARLIAMENTARY ELECTIONS OF 2019 IN THE REPUBLIC OF MOLDOVA - Савон, В. В.; Гринь, І. О. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2020)
The results of the parliamentary elections of 2019 in the Republic of Moldova and the features of the structure of the state power vertical are analyzed. Using mathematical methods, the results of the parliamentary elections were also analyzed, the main determinants of the prevailing political processes, the key regions of the main political forces were determined, the general political landscape of the republic was clarified and investigated, its main laws were determined.The problematic issues of the political life and structure of the Republic of Moldova were examined. The features of the electoral legislation of the country are established. The properties of the main political parties of the republic are analyzed. Some features of the course of the national election process are highlighted.The features of the main political parties, their electoral field, ideological orientation, the history of formation and inter-party relations are considered. The factors of influence on the will of Moldovan voters are investigated. In addition, an effective number of parties has been established in the Moldovan parliament.The configurations of potential coalitions in the Parliament of the Republic of Moldova are analyzed. The ethnic component in the political life of the country is clarified. The role of the regional factor in the electoral process is emphasized. The spatial and electoral similarity of parties in the 2019 parliamentary elections was determined. The features of the functioning of the political system of the country are highlighted. Particular attention is paid to the stability and capacity of possible coalitions and the success of potential coalition negotiations in general.The degree of regional homogeneity of the parties is clarified. The role of religion in the electoral process during the parliamentary elections of 2019 is determined. The results of mathematical calculations are analyzed and the results of the analysis are summed up.